Perspectivas de gestão participativa no setor de esporte e lazer da administração municipal de Vitória-ES - Santos, Marcel Ivan dos (2013)
This study investigated the planning and execution of the sports and leisure policies developed in the management of the Municipal Sport and Leisure of Victoria-ES (SEMESP) in the period 2005 to 2012, seeking explanations for the apparent distance of the management model based on participation citizen and intersectorial actions. Important is the intentionality that the discussion about different models of management, based on decentralization, citizen participation and intersectoral approach, all categories emerging from the 1980s. This is a qualitative study, which in its initial phase was conducted a literature review,, followed by analysis of documents concerning the management of SEMESP and possible partnerships, particularly with the Municipal Council of Sports (COMESP). The data analysis technique used was content analysis of Bardin (2009), by cutting the texts according to the most significant content. Thus, the main factors for the management of sport and leisure in the city Vitoria deviating from the perspective of social management is an approach to the ideas of nationalism that prevailed in the country about the sports policy from the 1960s, who coined the training of athletes and the sport of income. With regard to minimum participation in COMESP and SEMESP, we believe it is part of the limited understanding of some managers, and the community about the importance of leisure and sport evidenced in the lack of quorum at board meetings, and the devaluation of sport leisure front of other rights, insufficient training of citizens to participate, insufficient awareness of social commitment and struggle for collective gains and lack of commitment to public policy management of sport and leisure in general. Nevertheless, it can be said that the sports and leisure sector have advanced in order to promote access to citizens of these practices, given the diversity of equipment, projects and programs aimed at community capixaba of all age groups, but that in itself alone does not guarantee the right of ownership in this sector